Use of facial care products and frontal fibrosing alopecia: Coincidence or true association? - Waroonphan Leecharoen (2022)
The increasing incidence of frontal fibrosing alopecia (FFA) suggests that environmental factors may be related to the pathogenesis. Recent studies reported potential association between the use of facial care products and FFA. The aim of this study was to investigate the possible association between the use of facial care products and FFA in Asian females. A total of 250 females (50 FFA patients, 100 pattern hair loss [PHL] patients, and 100 normal controls) were recruited and completed a questionnaire to obtain information approximately facial care products and various environmental factors. Our study revealed the use of moisturizer to be significantly higher in the FFA group compared to normal controls (p < 0.001), and sunscreen use was significantly higher in the PHL group than in the control group (adjusted p < 0.001). Subjects with FFA or PHL reported significantly higher use of both sunscreen and moisturizer compared to normal controls (p < 0.001). This study focused on Asian populations. Our results revealed a high frequency of moisturizer and sunscreen use in both FFA and PHL among Asian females. Therefore, the use of facial care products appears not to be linked to the true disease mechanism of FFA, but rather to appearance-related concerns of patients.